A Comprehensive Study of Prestressing Steel and Concrete Variables Affecting Transfer Length in Pre-Tensioned Concrete Crossties - Bodapati, Naga N.B.; Peterman, Robert J.; Beck, B. Terry; Wu, Chih-Hang (Rural Railroad Safety Center, Kansas State University., 2021)
A comprehensive study was conducted to determine the variation of transfer length in pretensioned prestressed concrete railroad ties with varying prestressing steel types and concrete parameters. The in-depth evaluation included eighteen different prestressing reinforcement types that are employed in concrete railroad ties worldwide. The study consisted of two phases: Lab- Phase and Plant-Phase. Throughout the study, transfer lengths were determined from surface strain measurements on pre-tensioned concrete members. During the Lab-Phase, pre-tensioned concrete prisms were fabricated to replicate plant manufactured crossties. A special jacking arrangement was employed to ensure that each of the reinforcements was tensioned to the same force. Later, during the Plant-Phase, pre-tensioned concrete railroad ties were fabricated at a concrete crosstie manufacturing plant using the same reinforcements. In addition, a long-term study was conducted on plant-manufactured crossties to determine the variation of transfer length due to in-track loading.
Keywords: Concrete railroad ties; Crossties; Transfer length; Prestressed and pretensioned concrete; Indented wire